The effect of management decision processes on the management of bridges - Jamali, Amin; T. Adey, Bryan (Journal of Civil Engineering and Management, 2015)
It is necessary to execute interventions on bridges to ensure that they continue to provide an adequate level of service. It is necessary to inspect them to ensure that these interventions are timed appropriately. As there are negative impacts associated with both inspections and interventions, e.g. the impact on the owner due to the hours of labor and amounts of materials required to perform an inspection and execute an intervention, it is desirable to determine inspection and intervention strategies that minimize these negative impacts (i.e. the optimal management strategy). An important, however often overlooked, factor in determining optimal management strategies, is how management processes affect the determination of the optimal management strategy. In this article it is shown that it is not always possible to determine an optimal management strategy without explicitly taking into consideration management processes, how variations in management processes can be evaluated and that the significance of these variations is dependent on the values of the incurred impacts.First published online: 21 Oct 2015